2013
DOI: 10.4161/cib.23197
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical constraints and physical crowding direct collective migration of fibroblasts

Abstract: Migrating cells constantly interact with their immediate microenvironment and neighbors. Although studies on single cell migration offer us insights into the molecular and biochemical signaling pathways, they cannot predict the influence of cell crowding and geometrical cues. Using microfabrication techniques, we examine the influence of cell density and geometrical constraints on migrating fibroblasts. Fibroblasts were allowed to migrate on fibronectin strips of different widths. Under such conditions, cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…Cluster number normalized to total cell number was indeed significantly higher in BOKL co-culture BMSCs, as compared to other conditions (p < 0.001, Figure 2 E). We observed a preferential direction of cell migration in direct co-culture as compared to culture with CM or GM (p < 0.01, Figure 2 F), probably due to cell contact guidance [ 18 ] and not to specific characteristics of cells that composed the monolayer, being this effect evident also in co-culture with MRC-5. Figure 2 G reports the quantification of BOKL proliferation in the different conditions, showing no significant differences between BOKL co-culture BMSCs and BOKL CM BMSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Cluster number normalized to total cell number was indeed significantly higher in BOKL co-culture BMSCs, as compared to other conditions (p < 0.001, Figure 2 E). We observed a preferential direction of cell migration in direct co-culture as compared to culture with CM or GM (p < 0.01, Figure 2 F), probably due to cell contact guidance [ 18 ] and not to specific characteristics of cells that composed the monolayer, being this effect evident also in co-culture with MRC-5. Figure 2 G reports the quantification of BOKL proliferation in the different conditions, showing no significant differences between BOKL co-culture BMSCs and BOKL CM BMSCs.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is extremely relevant to the glioma situation, since glioma cells proliferate along blood vessels, creating an extremely dense environment. Using micropatterns, Leong et al. (2013 ) found that fibroblasts migrating on the sides of large lines adopt a spindle shape and migrate in a similar manner as on thin lines and suggested that an increase in cell density promotes cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Uniaxial migration was lost if the ECM line width exceeded 5 μm, and migration speed decreased (65). On very wide lines, the speed of fibroblasts migrating collectively decreased as the cells’ distance from the edge of the line increased (69). …”
Section: Experimental Models For Studying Cell Behavior In Confinementioning
confidence: 99%